Psychological peculiarities of the professional self-determination of social orphans in senior adolescence - Alimbayeva, R.; Baimukanova, M.; Sabirova, R.; Karipbaev, B.; Tamabayeva, M. (Routledge, 2018)
The purpose of this study was to investigate the psychological peculiarities of the professional self-determination of social orphans in senior adolescence. Two hundred sixty orphans aged 14–16, residing in Central Kazakhstan, were examined to determine the aptitude of orphan asylum adolescents to certain professions. Statistical analysis of male and female groups (p ≤ 0.002) found differences in the following characteristics. The typical spheres for girls were ‘individual-individual’ and ‘individual-imagery’. They focused on communication in professional activity and creativity. The typical spheres for girls were ‘individual-machinery’ and ‘individual – semiotic system’. Statistical differences were found in such professional spheres as law, transport, pedagogy, service sector, engineering, and electric engineering. The results of this study can be used in professional consultations and trainings for successful employment of social orphans.
Keywords: Professional selfdetermination; social orphan; employment; adolescent; Kazakhstan